2016
DOI: 10.1007/s10509-016-2987-6
|View full text |Cite
|
Sign up to set email alerts
|

Metallicity calibration and photometric parallax estimation: II. SDSS photometry

Abstract: We used the updated [Fe/H] abundances of 168 F-G type dwarfs and calibrated them to a third order polynomial in terms of reduced ultraviolet excess, δ 0.41 defined with ugr data in the SDSS. We estimated the M g absolute magnitudes for the same stars via the re-reduced Hipparcos parallaxes and calibrated the absolute magnitude offsets, ∆M g , relative to the intrinsic sequence of Hyades to a third order polynomial in terms of δ 0.41 . mean of the residuals and the corresponding standard deviation for the metal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…For the thin disk, most of the researchers found a negative metallicity radial gradient (e.g., Bilir et al 2012;Boeche et al 2013). In the vertical direction, Chen et al (2011), Carrell et al (2012), Li et al (2017), andTunçel et al (2017) found a negative metallicity gradient of the thick disk, while Katz et al (2011) and Li et al (2018) derived a flatter gradient. For the thin disk, a negative metallicity gradient was also found in the vertical direction Duong et al 2018), while Mikolaitis et al (2014 derived a flatter gradient.…”
Section: Introductionmentioning
confidence: 99%
“…For the thin disk, most of the researchers found a negative metallicity radial gradient (e.g., Bilir et al 2012;Boeche et al 2013). In the vertical direction, Chen et al (2011), Carrell et al (2012), Li et al (2017), andTunçel et al (2017) found a negative metallicity gradient of the thick disk, while Katz et al (2011) and Li et al (2018) derived a flatter gradient. For the thin disk, a negative metallicity gradient was also found in the vertical direction Duong et al 2018), while Mikolaitis et al (2014 derived a flatter gradient.…”
Section: Introductionmentioning
confidence: 99%
“…The (u−g) 0 and (g −r) 0 colour indices of these stars, taken from Tunçel Güçtekin et al (2017), are used to estimate their U V -excess, δ, which provide [α/Fe] elements via our calibration, i.e. Eq.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The star sample consists of 23,414 F and G dwarfs taken from Tunçel Güçtekin et al (2017) which were provided by a series of constraints explained in the following. The star sample was defined with Galactic coordinates 85…”
Section: The Star Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Carney 1979;Karaali et al 2003a, b, c;Karataş & Schuster 2006;Karaali et al 2011;Tunçel Güçtekin et al 2016;Çelebi et al 2019). Similar calibrations have been developed for the SDSS photometric system and applied to faint stars (Karaali et al 2005;Bilir et al 2005;Tunçel Güçtekin et al 2017). These calibrations were used to calculate metal abundances (Ak et al 2007;Ivezic et al 2008;Tunçel Güçtekin et al 2019) and estimation of the Galactic model parameters…”
Section: Introductionmentioning
confidence: 99%